Long-Term Outcomes and Causes of Death in Patients With Renovascular Disease Undergoing Renal Artery Stenting. (August 2016) - Wallace, Eric L.; Tasan, Ediz; Cook, Bryon S.; Charnigo, Richard; Abdel-Latif, Ahmed K.; Ziada, Khaled M.
Renovascular disease (RVD) can lead to hypertension and chronic kidney disease (CKD). Patients with advanced peripheral arterial disease (PAD) have a 5-year mortality of ∼30%. Rate and causes of death in patients with significant RVD, who share similar risk factors with patients having PAD, are not well defined. We assessed consecutive patients with RVD who underwent renal artery stenting at our institution over 6 years. Specific causes of death were ascertained, and the probability of survival was estimated. Cox models were fit to identify predictors of outcomes. We identified 281 patients with RVD who underwent renal stenting. Follow-up was available for all patients (median 5.1 years). All-cause mortality was 24.2% at 5 years and 33.7% at 7 years (compounded annualized death rate: 5.5%). Of the 68 deaths, 36 (52.9%) were cardiovascular (13.2% acute myocardial infarction, 13.2% stroke, 11.8% sudden death, and 10.3% congestive heart failure) and 32 (47.1%) deaths had noncardiovascular causes. In patients with RVD undergoing stenting, cardiovascular events are the most common causes of death. Compared to patients with advanced PAD, RVD may have a lower 5-year mortality.